Neuromodulation of swarming behavior in Caenorhabditis elegans : Insights into the conserved role of calsyntenins - Navneet Shahi; Nisha Kumari; Sharveri Khapre; Dimple Dahiya; Egemen Saritekin; Aşkın Kocabaş; Kavita Babu (Proceedings of the National Academy of Sciences, 2026)
Collective animal behaviors arise from a complex interplay between internal physiological states and external environmental cues. In Caenorhabditis elegans , favorable conditions promote dispersal, while stressors like food scarcity trigger aggregation. Here, we describe a distinct self-organized swarming behavior, where C. elegans move and feed in groups driven by uncontrolled local increases in population density despite abundant food availability. While various environmental factors have been implicated in collective behaviors in C. elegans , the underlying genetic and molecular mechanisms remain unclear. We identify a key role for the conserved calsyntenin protein CASY-1 in regulating swarming. Through genetic, behavioral, and optogenetic approaches, we show that CASY-1 functions to modulate the neuropeptide pigment-dispersing factor (PDF) signaling. Mutants in casy-1 show impaired PDF-1 signaling and reduced inhibition of the serotonin pathway, a known regulator of social behaviors. This dysregulation, along with its associated mechanosensory and foraging defects, likely contributes to the swarming phenotype. Our findings reveal a putative neuromodulatory pathway critical for swarming behavior in C. elegans .